Meta-Analysis the Effect of Hormonal Contraception on Sexual Disfunction in Injection and Oral Contraceptive Acceptors - Sumiyati, Sumiyati; Budihastuti, Uki Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: One of the factors that cause sexual dysfunction is the use of hormonal contraception. The hormone progesterone in contraceptives functions to thicken cervical mucus. In addition, the hormone progesterone also facilitates the conversion of carbohydrates into fat so that one of the side effects is causing body weight to increase and reducing sexual arousal which causes an effect on sexual desire. This study aimed to analyze the effect of the use of injectable hormonal contraception and pills on the incidence of sexual dysfunction using a meta-analysis study. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flowchart diagram. The process of searching for articles was carried out with a range of 2011-2022 in the Google Scholar, PubMed, Science Direct, Researchgate and Springerlink databases. The keywords used in the article search are “hormonal contraceptive” AND “oral contraception” OR “pills contraceptive” AND “injectable contraceptive” AND “sexual dysfunction” AND “cross-sectional”. The inclusion criteria are full text articles with cross-sectional study design, articles using English, multivariate analysis with Adjusted Odds Ratio. Articles that met the requirements were analyzed using the RevMan 5.3 application. Results: A total of 14 articles with a cross-sectional study design originating from Iran, Indonesia, Malaysia, Ethiopia, Egypt, Washington, Sweden and Polan were meta-analyzed in this study. A meta-analysis of 7 articles showed that there was an effect of using injectable hormonal contraception on the incidence of sexual dysfunction 1.66 times compared to those not using injectable contraception, but this was not statistically significant (aOR= 1.66; 95% CI= 0.65 to 4.26; p= 0.290). Meanwhile, 7 articles showed that women using oral contraceptives had a 1.42 times risk of experiencing sexual dysfunction compared to not using oral contraceptives and this was statistically significant (95% CI= 1.04 to 1.92; aOR= 1.42; p= 0.030). Conclusion: Injectable hormonal contraceptives show that there is an effect on the incidence of sexual dysfunction, but statistically this relationship is not significant. Hormonal contraceptive pills showed an effect on the incidence of sexual dysfunction and was statistically significant. Keywords: sexual dysfunction, injectable contraceptives, oral contraceptives, meta-analysis. Correspondence:Sumiyati. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: mia.azizi.ma@gmail.com. Mobile: +6282282246211.